Microstructural and Mechanical Characterization of Alloys - Sroka, Marek; Golański, Grzegorz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains manuscripts related to alloys (engineering materials) to discuss potential materials, methods for improvement of the strength and cyclic properties of alloys, the stability of microstructures, the possible application of new (or improved) alloys, and the use of treatment for alloy improvement. The broad spectrum of topics included in the articles of this Special Issue demonstrates that research into the microstructural and mechanical characteristics of alloys represents a contemporary field. These topics are also envisaged to be of interest to scientists in other research centers, and we can still expect new developments in this investigation field.